Determinants of Purchasing Decisions for the Erigo Brand on the Shopee Application - Rudi Laksono; Fikri Maulana (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to describe and analyze the effect of price and product quality on purchasing decisions of Erigo fashion products on the Shopee application, both partially and simultaneously. This research employed a survey approach using descriptive and quantitative methods. Data were collected through questionnaires distributed to 50 students of the Institut Bisnis dan Informatika Kosgoro 1957 and analyzed using SPSS version 26. The validity test results indicate that all questionnaire items have Corrected Item–Total Correlation (CITC) values above 0.30, while the reliability test results show that the Cronbach’s Alpha values for all variables are greater than 0.60, indicating that the research instruments are valid and reliable. Descriptive analysis results show that the price variable has the highest score of 211, reflected by the discount or promotion dimension with the indicator of discounted price and promotion. The product quality variable also records the highest score of 211, reflected by the feature dimension with the indicator of features that facilitate ease of use, while the lowest score is found in the durability indicator at 181. For the purchasing decision variable, the highest score of 218 is reflected by the information search dimension with the indicator of pre-purchase information-seeking activity. Hypothesis testing results reveal that price has a positive and significant effect on purchasing decisions, as indicated by a t-value of 6.099, which is greater than the t-table value of 2.012. Product quality also shows a positive and significant effect with a t-value of 2.256, which is greater than the t-table value of 2.012. Simultaneously, price and product quality have a significant effect on purchasing decisions, as indicated by an F-value of 112.410, which is greater than the F-table value of 3.20, and a coefficient of determination (R²) of 0.845, meaning that 84.5% of the variation in purchasing decisions can be explained by price and product quality. Therefore, the purchasing decisions of students toward Erigo products on Shopee are primarily influenced by competitive pricing through promotional programs and product quality reflected in ease-of-use features, although product durability still needs improvement.